2008
DOI: 10.1080/10915810802513502
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Toxicological Potential of Capsinoids: IV. Teratology Studies of CH-19 Sweet Extract in Rats and Rabbits

Abstract: In order to evaluate the safety of CH-19 Sweet extract that contains capsinoids, teratology studies were conducted in pregnant Sprague-Dawley rats (20 rats per group) and pregnant New Zealand white rabbits (17 to 22 animals per group). The test substance was administered to rats by gavage for 11 days on gestation days 7 to 17 at doses of 0 (vehicle), 1.25, 2.5, and 5.0 ml/kg and to rabbits for 13 days on gestation days 6 to 18 at doses of 0 (vehicle), 0.25, 0.5, and 1.0 ml/kg. As the concentration of capsinoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Dihydrocapsiate (80.75 mg/kg/day) was administered as part of the CH-19 Sweet extract (5 ml/kg/day) employed as the high dose in a two-generation reproduction study (Kodama et al 2008a) and a teratology study (Bernard et al 2008b), both in rats. In the reproduction study, dihydrocapsiate administration was started 8 weeks before the start of mating for F o males, 2 weeks before the start of mating for F o females, and on the day of weaning (day 21 after birth) for F, rats.…”
Section: Discussionmentioning
confidence: 99%
“…Dihydrocapsiate (80.75 mg/kg/day) was administered as part of the CH-19 Sweet extract (5 ml/kg/day) employed as the high dose in a two-generation reproduction study (Kodama et al 2008a) and a teratology study (Bernard et al 2008b), both in rats. In the reproduction study, dihydrocapsiate administration was started 8 weeks before the start of mating for F o males, 2 weeks before the start of mating for F o females, and on the day of weaning (day 21 after birth) for F, rats.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded the NOAEL of dihydrocapsiate for general toxicity in dams, reproductive functions of dams, and embryofetal development was judged to be 1000 mg/kg/day both in rats and rabbits. Bernard et al (2008a) performed a similar study using CH-19 Sweet extract using the same test subjects and days of and route of test article administration. The dose levels employed were 0 (vehicle), 1.25, 2.5, and 5.0 ml/kg in the rat and 0 (vehicle), 0.25, 0.5, and 1.0 ml/kg in the rabbit.…”
Section: Malesmentioning
confidence: 99%
“…This same amount of dihydrocapsiate (81 mg/kg/day) was administered as part of the CH-19 Sweet extract (5 nil/kg/day) employed as high doses in a two-generation reproduction study (Kodama et al 2008a) and a teratology study (Bernard et al 2008), both in rats. In the reproduction study, dihydrocapsiate administration was started 8 weeks before the start of mating…”
Section: General Descriptionsmentioning
confidence: 99%